Determinan Pergeseran Tenaga Kerja Sektor Pertanian ke Sektor Non-Pertanian Studi Kasus di Indonesia - Nurul Raiyan; Novia Dwi Kumala Putri (Politeknik Statistika STIS, 2021)
The agricultural sector has an important role in the national economy in Indonesia, especially in accommodating the labor. The contribution of the agricultural sector to economic growth has decreased in the last few years, especially from 2011 to 2019. On the other hand, it still should accommodate more workers than it should be. It shows that there is inequality in Indonesia’s economic structure. This research used the Two Stage Least Square (2SLS) method to estimate whether or not the simultaneous relationship between economic growth and the shifting labor from the agricultural sector to nonagricultural sectors. The result shows that there is a simultaneous relationship between economic growth and labor shifting. On the other hand, economic growth and domestic investment in the agricultural sector significantly has negative effects towards the percentage of labor who work in the agricultural sectors. Furthermore, the HDI significantly has a positive effect on economic growth.